Health Equity and Disparities in ROP Care: A Need for Systematic Evaluation - Ndukwe, Tochukwu; Cole, Emily; Scanzera, Angelica C.; Chervinko, Margaret A.; Chiang, Michael F.; Campbell, John Peter; Chan, Robison Vernon Paul (Frontiers in Pediatrics, 2022)
Retinopathy of prematurity (ROP) is a vasoproliferative retinal disorder that can have devastating visual sequelae if not managed appropriately. From an ophthalmology standpoint, ROP care is complex, since it spans multiple care settings and providers, including those in the neonatal intensive care unit (NICU), step down nurseries, and the outpatient clinic setting. This requires coordination and communication between providers, ancillary staff, and most importantly, effective communication with the patient’s family members and caregivers. Often, factors related to the social determinants of health play a significant role in effective communication and care coordination with the family, and it is important for ophthalmologists to recognize these risk factors. The aim of this article is to 1) review the literature related to disparities in preterm birth outcomes and infants at risk for ROP; 2) identify barriers to ROP care and appropriate follow up, and 3) describe patient-oriented solutions and future directions for improving ROP care through a health equity lens.